Habitat quality, not habitat amount, drives mammalian habitat use in the Brazilian Pantanal - Regolin, André Luis [UNESP]; Oliveira-Santos, Luiz Gustavo; Ribeiro, Milton Cezar [UNESP]; Bailey, Larissa Lynn (My University, 2021)
Context: An understanding of species-habitat relationships is required to assess the impacts of habitat fragmentation and degradation. To date, habitat modeling in fragmented landscapes has relied on landscape composition and configuration metrics and the importance of habitat quality in determining species distributions has not been sufficiently explored. Objectives: We evaluated how habitat use by herbivores and frugivorous mammals is shaped by a potential interaction of habitat amount and quality in the Brazilian Pantanal wetland. We also assessed if the contribution of habitat quality to species´ habitat use varies according to the species sensitivity to habitat loss. Methods: We combined mammal detection data obtained from camera traps with thematic maps to estimate the amount of habitat and measured habitat quality using local environment variables and distance to waterbodies. Specifically, we used a single-season occupancy approach to evaluate the relative support of univariate, additive, and interactive relationships between species-specific habitat use and measures of habitat quality and quantity. Results: Habitat quality was more important than habitat amount in determining species habitat use (occupancy) in a naturally fragmented landscape. Habitat quality alone was the best predictor of habitat use for two of the six species (white lipped peccary and collared peccary), but no species’ habitat use was explained solely by habitat amount. Habitat amount was influential only when considered in conjunction with habitat quality covariates and only for two sensitive species to habitat loss (agouti and red brocket deer). Habitat quality alone was the best predictor of habitat use for two of the less sensitive species (white lipped peccary and collared peccary). Habitat use for two species was not explained by any covariate (tapir and gray brocket deer). Conclusions: Conservation programs should incorporate both habitat quality and amount when dealing with sensitive species and prioritize habitat quality management when focusing in less sensitive species.
Keywords: Artiodactyla; Habitat degradation; Habitat modeling; Perissodactyla; Rodentia; Wetland